Construction of Epstein-Bar virus cocktail peptide fused with Fcγ of IgG: as a potential delivery system for vaccine development. Issue 1 (1st January 2019) - Amel Jamehdar, Saeid; Tabaei, Samira; Mashkani, Baratali; Karimi, Reza; Motallebnezhad, Morteza; Esmaili, Arezoo
ABSTRACT: Epstein–Barr virus (EBV) associated with several diseases such as contagious mononucleosis chronic active EBV infection, and diverse sorts of malignant tumors. Therefore, using applicable vaccines could be advantageous for public health. Yet, the vaccine has been unavailable to protect from EBV so far. In the current study, to develop a multi-peptide vaccine for EBV and assess its expression in Pichia pastoris yeast system, three immunodominant sequences in glycoprotein (gp) 85, gp350 and latent membrane protein 1 (LMP1) were chosen. To construct fusion peptide, -GGGGS- liker was applied. After cloning the fusion peptide in the pPICZαA expression vector, this recombinant vector processed and transfected into Pichia pastoris host cells. The expression of high level of EBV fusion peptide was confirmed by dot blot and SDS-PAGE procedures. The Pichia pastoris is capable of supporting EBV fusion peptide expression. The application of this fusion peptide as a peptide vaccine to fight EBV is suggested.